1997
DOI: 10.1128/jvi.71.4.2772-2778.1997
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered live attenuated influenza A virus vaccine candidates

Abstract: We have generated new influenza A virus live attenuated vaccine candidates by site-directed mutagenesis and reverse genetics. By mutating specific amino acids in the PB2 polymerase subunit, two temperature-sensitive (ts) attenuated viruses were obtained. Both candidates have 38؇C shutoff temperatures in MDCK cells, are attenuated in the respiratory tracts of mice and ferrets, and have very low reactogenicity in ferrets. Infection of mice or ferrets with either mutant conferred significant protection from chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 50 publications
1
7
0
4
Order By: Relevance
“…Both high-level HI and neutralizing activities were easily elicited by codon-optimized DNA vaccines. The titers of protective antibodies achieved in this report were not only significantly improved over that from early versions of flu DNA vaccines (2,9,18,22,50) but also comparable to or higher than those of positive anti-HA sera reported in previous animal studies with various flu vaccines, including recombinant viral vector-based flu HA vaccines (16,30,39) and inactivated and live flu vaccines (23,38,42).…”
Section: Discussionsupporting
confidence: 77%
“…Both high-level HI and neutralizing activities were easily elicited by codon-optimized DNA vaccines. The titers of protective antibodies achieved in this report were not only significantly improved over that from early versions of flu DNA vaccines (2,9,18,22,50) but also comparable to or higher than those of positive anti-HA sera reported in previous animal studies with various flu vaccines, including recombinant viral vector-based flu HA vaccines (16,30,39) and inactivated and live flu vaccines (23,38,42).…”
Section: Discussionsupporting
confidence: 77%
“…However, with the advancement in biotechnology, it may be possible to consider new vaccine approaches using genetically engineered live virus. For example, several experiments showed the possibility of attenuating influenza virus by introducing changes in the PB2 gene, exchanging the promoter region of the NA gene with a different promoter, and generating influenza viruses that have truncated NS1 genes (Muster et al, 1991;Murphy et al, 1997;Parkin et al, 1997;Talon et al, 2000). Our study with TK/OR/71-del, which has truncated NS1 protein, showed attenuation in pathogenicity and a decreased ability to replicate in chickens (Cauthen et al, 1999).…”
Section: Live Vaccinesmentioning
confidence: 73%
“…Опыты, проведенные некоторыми исследователями [12,18], показали высокую эффективность включения сайт-специфических мутаций в РВ2-ген вирулентного штамма для получения аттенуированных вариантов вируса гриппа А. Применение этой технологии в отношении РВ2-гена позволило включать в этот ген несколько аттенуирующих мутаций, что дало возможность контролировать степень аттенуации вирулентного штамма. Данные, полученные этими авторами, свидетельствовали также о высокой генетической стабильности некоторых из этих вариантов, полученных с помощью данной технологии.…”
Section: в в е д е н и еunclassified